2010
DOI: 10.1111/j.1708-8208.2009.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant Placement in Patients with Oral Bisphosphonate Therapy: A Case Series

Abstract: Within the limitations of this study, it could be concluded that neither being on oral bisphosphonate treatment before implant placement nor starting bisphosphonate therapy after implant installation might jeopardize the successful osseointegration and clinical and radiographic condition of the implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(53 citation statements)
references
References 17 publications
3
47
0
3
Order By: Relevance
“…Other studies have reported findings consistent with these results; three-fourths of implants of the to-date published cases of BRONJ in association with implant insertion were placed in the posterior jaw [14,16,20]. The influence of implant location may as well explain the low rates of osteopathology found in some other studies such as that of Shabestari et al [31]. They analyzed 21 female patients with osteoporosis who received oral BP therapy after the placement of 46 dental implants and found no case of BRONJ.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other studies have reported findings consistent with these results; three-fourths of implants of the to-date published cases of BRONJ in association with implant insertion were placed in the posterior jaw [14,16,20]. The influence of implant location may as well explain the low rates of osteopathology found in some other studies such as that of Shabestari et al [31]. They analyzed 21 female patients with osteoporosis who received oral BP therapy after the placement of 46 dental implants and found no case of BRONJ.…”
Section: Discussionsupporting
confidence: 65%
“…A few retrospective case series or cohort studies have examined the incidence of osteopathology associated with BP therapy and implant insertion [15,19,28,31,33]. In 2010, Koka et al published a retrospective review that examined implant survival in 55 postmenopausal women who received oral BP therapy in comparison with a control group of 82 women who did not receive BP therapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of dentures vs. implants. It is suggested to not place immediate implants in patients with antiresorptive therapy, atraumatic surgery with perioperative antibiotics, the necessity of a recall and the avoidance of bone augmentations Grötz 2010 [54]ReviewThe authors provide an algorithm how to proceed with patients receiving BP seeking implant therapy.The authors state the necessity for an individual risk assessment and avoidance of bone augmentations Krimmel 2014 [55]RS50 patients with BP-ONJDMFT of all patients 20.5 ± 4.2disease free interval for patients with DMFT < 20: 39.7 ± 1.1 monthsdisease free interval for patients with DMFT > 20: 14.4 ± 2.8 monthsThe DMFT had no influence on the overall healing rate of BP-ONJ Tsao 2013 [56]CCS63 patients22 BP-ONJ patients41 matched controlsCaries similar between groupsPeriodontal disease associated with BP-ONJ (pocket depth, IgG serum titer against Porphyromonas gingivalis, IL 1ß level in gingival cervical fluid) Thumbigere-Math 2013 [57]CCS73 patients25 BP-ONJ patients 48 matched controlsBP infusions BP-ONJ 38.4 and control 18.8BP-ONJ vs control:missing teeth: 7.8 vs 3.1clinical attachment level: 2.18 vs 1.56radiogic bone loss at teeth > 50%: 20% vs. 6% Martin 2010 [58]CSS8,752 patients with oral BP returned dental survey (62% response rate)589 patients with dental implants16 patients with 26 implant failures8 patients with failure of 12 implants in the maxilla9 had failure with 14 implants in the mandible Shabestari 2009 [59]RS21 female osteoporotic women with oral BP and 46 implantsNo BP-ONJ, no signs of peri-implantitis Zahid 2011 [60]RS362 patients with implants26 BP patients with 51 implants3 implants failedPatients with BP had more thread exposure Memon 2012 [61]RS200 patientsBP: 100 women with 153 implantscontrol: 100 women with 132 implantsSuccess equal for both groups 93.5 (BP) vs. 95.5 (control)crestal bone change from implant insertion to stage two surgery: no difference between the groups Yip 2012 [62]CCS337 patients 114 patients with implant failure223 patients without implant failure% of patients using BPImplant failure group: 9.65%no implant failure: 4.04 Walter 2014 [3]RS504 patients with osteonecrosis227 with BP-ONJ7 out of 227 patients with BP-ONJ implant as trigger factor…”
Section: Resultsmentioning
confidence: 99%
“…As the latent negative effect of osteoporosis on dental implants, many drugs including estrogen [9] , simvastatin [16] , biphosphonates [18][19][20] , as well as growth factors including bone morphogenic proteins [21] and basic fibroblast growth factor (FGF) [18] , have been explored to promote bone healing and osseointegration of dental implants under osteoporosis, and many positive results have been obtained. Biphosphonates are a group of medicine commonly used for treatment of osteoporosis and have strong effects on inhibition of osteoclast-mediated bone resorption, and even lead to osteoclast death (apoptosis).…”
Section: Discussionmentioning
confidence: 99%